Optimasi Pemakaian Steam pada Proses Refinery CPO dengan Pendekatan TPM Focus Improvement - Arif Budi Sulistyo; Hartadi Wijaya; Nur Hidayanti; Fikri Fadhilah (Journal of Industrial View, 2025)
PT. MNA is a partner in the palm oil processing industry and its derivatives, primarily aimed at producing cooking oil. The refinery process of Crude Palm Oil (CPO) is one of the production stages that requires high energy consumption, particularly in the form of steam. This study aims to identify the level of steam usage in the refinery process and to explore opportunities for optimization and energy savings. The methods used include the Kaizen approach and Total Productive Maintenance (TPM). Initial analysis showed that steam consumption at PT. MNA reached 204,000 kg per month, with the highest usage occurring in the steam drying SBE process (82.97%), followed by steam heating PHE (10.82%), and steam heating hot water (6.21%). Based on a Pareto analysis, the improvement focus was placed on the steam drying SBE process. The implementation of improvements through reducing process time from 850 seconds to 700 seconds proved effective without disrupting other processes. As a result, steam consumption was successfully reduced to 168,000 kg per month, while the oil content in SBE remained within the company’s target of 20–22%. Therefore, the TPM Focus Improvement and Kaizen approaches have been proven effective in optimizing steam usage in the CPO refinery process.    PT. MNA sebagai mitra bidang pengolahan minyak kelapa sawit dan turunannya untuk menghasilkan minyak goreng. Proses refinery Crude Palm Oil (CPO) merupakan salah satu tahapan produksi yang memerlukan konsumsi energi dalam jumlah besar, terutama dalam bentuk steam. Penelitian ini bertujuan untuk mengetahui tingkat penggunaan steam pada proses refinery serta mengidentifikasi peluang optimasi dan penghematan energi. Metode yang digunakan meliputi pendekatan Kaizen dan TPM (Total Productive Maintenance). Hasil analisis awal menunjukkan bahwa konsumsi steam di PT. MNA mencapai 204.000 kg per bulan, dengan penggunaan terbesar terdapat pada proses steam drying SBE sebesar 82,97%, disusul steam heating PHE sebesar 10,82% dan steam heating hotwater sebesar 6,21%. Berdasarkan analisis Pareto, fokus perbaikan difokuskan pada proses steam drying SBE. Implementasi perbaikan dengan pengurangan waktu proses dari 850 detik menjadi 700 detik terbukti efektif tanpa mengganggu proses lainnya. Hasilnya, konsumsi steam berhasil dikurangi menjadi 168.000 kg per bulan, serta kadar oil content pada SBE tetap berada dalam target perusahaan yaitu 20–22%. Dengan demikian, pendekatan TPM Focus Improvement dan Kaizen terbukti efektif dalam mengoptimalkan pemakaian steam pada proses refinery CPO.